Response of different varieties of cereals to inoculation with Bradyrhizobium sp. - Bécquer Granados Carlos José; Nápoles Gómez José Ángel; Álvarez Orquidea; Ramos, Yamilka; Quintana, Maribel; Galdo, Yaldreisi (Revista Mexicana de Ciencias Agrícolas, 2018)
Two field experiments were performed in 2009 at the Experimental Station of Pastures and Forages Sancti Spiritus, Cuba (21° 53’ 00” north, 79° 21’ 25” west longitude and 40 m) to determine the response of different varieties of cereals to bio-fertilization with Bradyrhizobium sp. The preparations of inocula and seed inoculation were made according to preset methodologies for this field of study. The experimental design was through split-plots and 4 replicates per treatment. The fertilized control was applied with nitrogen (150 kg N ha-1) and agronomic variables were evaluated. We applied two- factor analysis of variance; the differences between means were determined by Duncan and t-student comparison. In the experiment with Triticum, we concluded that, the treatment with the best responses was Triticale- inoculated and IRM37-inoculated and that, Triticum secale exceeded on root dry weight and stem length compared with T. aestivum, which makes this first promising species for drought conditions. In the experiment with Zea mays is concluded that, even though air dry weight treatments were best with chemical fertilization, in dry weight of the ear Canilla-inoculated treatment showed statistically equal to that of the fertilized treatments, so it ́s considered a positive response of this variety to bio-fertilization. However, the inf luence of indigenous rhizosphere bacteria in some of the studied variables is not ruled out.